Horizontal subsurface flow constructed wetland for removal of high-loaded ibuprofen from wastewater under tropical climate - Li, Yifei (2015)
Performance of a horizontal subsurface flow constructed wetland system for treatment of wastewater spiked with high-loaded ibuprofen (IBP) over 342 days under tropical climate was studied. The system consisted of a planted bed with Typha angustifolia and an unplanted bed, showing high removal efficiencies of COD, NH4+-N, TP and IBP. Typha angustifolia positively influenced the removal of NH4+-N, TP and IBP and indicated a uniform role in uptake and accumulation of IBP. Detection of IBP metabolites including carboxylic acid ibuprofen, 2-hydroxy ibuprofen, and 1-hydroxy ibuprofen in water and leaf tissues demonstrated the plant uptake and microbial degradation of IBP. The bacterial diversity and evenness in wetlands implied the stronger resistance of bacterial communities in the planted bed to the high loading. Some sulfate-reducing bacteria were most possibly responsible for the microbial biodegradation of IBP, such as Cytophaga sp., Sphingobacteriales, and Cytophagales in the planted bed, while Cytophaga sp. and Desulfobacterium sp. in the unplanted bed.